Consumer value co-creation in online business: the case of global travel services - Smaliukiene, Rasa; Chi-Shiun, Lai; Sizovaite, Indre (Journal of Business Economics and Management, 2014)
This paper aims to examine the application of value co-creation approach in online travel service based on service-dominant logic. Drawing on recent works, the research indicates travellers as co-creators of value and emphasizes the development of customer–supplier interaction. The paper presents three case studies to analyse global travel service suppliers’ (service providers) behaviour: CouchSurfing International, Inc.; TripAdvisor LLC, AirBnbINc. Case studies analysis is followed by netnographic research of 22 different discussions (1243 records) in online forums related to selected service suppliers. The research findings suggest that value co-creation approach can be effectively used to analyse processes in global online travel service section. The originality of the paper lies in exploring the contribution of co-creation approach which allowed to identify the patterns of actions and behaviour of the online travel service providers and their consumers. As an additional value of the research, it was found that the online travel service providers integrate customer-to-customer interactions as a value co-creation in their platforms using consumers’ resources such as time, knowledge and experience.